Gait analysis after total hip arthroplasty with leg‐length equalization in women with unilateral congenital complete dislocation of the hip – comparison with untreated patients - Kou‐An Lai; Chaofan Lin; I‐Ming Jou; Fong‐Chin Su (2001)
Abstract Patients with Crowe Type‐IV congenital dislocation of the hip (CDH) show significant clinical improvement after total hip arthroplasty (THA) because this surgery greatly reduces pain. Concomitant leg‐length equalization in unilateral patients — a controversial procedure — theoretically should significantly improve these patients' ability to walk efficiently and comfortably. To understand the impact of leg‐length equalization on these patients, we compared their gait parameters with those of untreated patients without pain but with leg‐length discrepancy. Using a motion analysis system, three force platforms and computer calculation, the gait parameters during level walking of 22 women with unilateral Crowe Type‐IV CDH were studied at an average of 58 months (27–98 months) following a successful cementless THA. The socket was placed in the best bone stock, which was close to the level of the true acetabulum. The leg‐length discrepancy was equalized to within 2 cm in all patients. The Harris hip score averaged 94.8 (range, 88–100) at the time of the study. Nine women with untreated unilateral Crowe Type‐IV CDH without major pain but with an average leg‐length discrepancy of 4.7 cm (range, 2.5–6 cm) were also studied for comparison. The treated subjects (Group 1; THA and leg‐length equalization) walked faster and had gait parameters with better bilateral symmetry than the untreated subjects (Group 2). We concluded that leg‐length equalization in addition to THA in patients with unilateral Crowe Type‐IV CDH significantly improves gait symmetry and efficiency. © 2001 Orthopaedic Research Society. Published by Elsevier Science Ltd. All rights reserved.